2022
DOI: 10.1094/pdis-04-21-0763-re
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pyrenophora tritici-repentis in Tunisia and Comparison with a Global Pathogen Population

Abstract: Pyrenophora tritici-repentis (Ptr) causes tan spot, an important foliar disease of wheat. A collection of Ptr isolates from Tunisia, located in one of the main secondary centers of diversification of durum wheat, was tested for phenotypic race classification based on virulence on a host differential set, and for the presence of the necrotrophic effector (NE) genes ToxA, ToxB , and toxb by PCR analysis. While races 2, 4, 5, 6, 7, and 8 were identified according to their virulence phenotypes, PCR testing indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…As a part of the evaluation process, infected wheat leaves and debris were collected and analyzed morphologically to confirm the presence of Ptr . The identification of typical conidia of Ptr from collected leaf samples confirmed the infection with tan spot ( Figure S3 ), and several obtained isolates have been published in Laribi et al [ 24 , 25 ]. In addition, the collected debris contained spherical black pseudothecia visible to naked eyes.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…As a part of the evaluation process, infected wheat leaves and debris were collected and analyzed morphologically to confirm the presence of Ptr . The identification of typical conidia of Ptr from collected leaf samples confirmed the infection with tan spot ( Figure S3 ), and several obtained isolates have been published in Laribi et al [ 24 , 25 ]. In addition, the collected debris contained spherical black pseudothecia visible to naked eyes.…”
Section: Resultssupporting
confidence: 72%
“…Recent studies on Pyrenophora tritici-repentis in Tunisia revealed high phenotypic and genotypic diversity of Ptr in Tunisia. Hence, phenotyping wheat populations from the Mediterranean region under favorable conditions can lead to the discrimination between resistant and susceptible accessions [ 14 , 19 , 24 , 25 ]. In this study, 549 wheat accessions that comprised mainly landraces from five Mediterranean countries were assessed for resistance/susceptibility to TS disease in Tunisia over two cropping seasons at the adult stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations